Apolipoprotein B48 metabolism in chylomicrons and very low‐density lipoproteins and its role in triglyceride transport in normo‐ and hypertriglyceridemic human subjects - Björnson, E.; Packard, C.J.; Adiels, M.; Andersson, L.; Matikainen, N.; Söderlund, S.; Kahri, J.; Hakkarainen, A.; Lundbom, N.; Lundbom, J.; Sihlbom, C.; Thorsell, A.; et al. (Journal of internal medicine, 2020)
Background Renewed interest in triglyceride‐rich lipoproteins as causative agents in cardiovascular disease mandates further exploration of the integrated metabolism of chylomicrons and very low‐density lipoproteins (VLDL). Methods Novel tracer techniques and an integrated multi‐compartmental model were used to determine the kinetics of apoB48‐ and apoB100‐containing particles in the chylomicron and VLDL density intervals in 15 subjects with a wide range of plasma triglyceride levels. Results Following a fat‐rich meal, apoB48 appeared in the chylomicron, VLDL1 and VLDL2 fractions in all subjects. Chylomicrons cleared rapidly from the circulation but apoB48‐containing VLDL accumulated, and over the day were 3‐fold higher in those with high versus low plasma triglyceride. ApoB48‐containing particles were secreted directly into both the chylomicron and VLDL fractions at rates that were similar across the plasma triglyceride range studied. During fat absorption, whilst most triglyceride entered the circulation in chylomicrons, the majority of apoB48 particles were secreted into the VLDL density range. Conclusion The intestine secretes apoB48‐containing particles not only as chylomicrons but also directly into the VLDL1 and VLDL2 density ranges both in the basal state and during dietary lipid absorption. Over the day, apoB48‐containing particles appear to comprise about 20–25% of circulating VLDL and, especially in those with elevated triglycerides, form part of a slowly cleared ‘remnant’ particle population, thereby potentially increasing CHD risk. These findings provide a metabolic understanding of the potential consequences for increased CHD risk when slowed lipolysis leads to the accumulation of remnants, especially in individuals with hypertriglyceridemia.